Optimising the care of the trapped patient following a motor vehicle collision: A UK-Based Delphi consensus study - Tim Nutbeam; Rob Fenwick; Ian Marritt; Brian Lee; Luke Staveley-Wadham; Nigel Lang; Louise Johnson; Nicolas Mattock; Jane Ogilvie; Emily Foote; Francis Screech; Lara Lebeau-Humarau; et al. (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Motor vehicle collisions (MVCs) are a leading cause of injury and death worldwide. Up to 40% of casualties may become trapped and entrapment is associated with delayed care and worse outcomes. There is little national or international consensus guiding the care of physically trapped patients who cannot self-extricate. This study aimed to develop multidisciplinary consensus-based principles to optimise clinical and operational care for trapped patients following MVC. Methods A three-round Delphi study was conducted from January to March 2025, following the CREDES framework. A multi-professional steering group developed preliminary statements informed by literature review and expert consultation. Subject matter experts (SMEs) with operational experience in extrication, prehospital, and trauma care were recruited through stakeholder organisations. Statements were refined iteratively through SME feedback. Consensus was defined as ≥ 70% agreement or disagreement. Statements reaching consensus were removed from subsequent rounds; others were revised based on free-text feedback. Results Sixty-six SMEs participated, with high engagement across all three rounds. Consensus was achieved for 104 statements covering standardised extrication terminology, prioritisation of time-sensitive extrication for critically injured patients, minimisation of unnecessary on-scene interventions, emphasis on early psychological support for trapped casualties, and the importance of interdisciplinary communication and coordination. The consensus supports a paradigm shift towards rapid, patient-centred extrication, balancing clinical needs, operational realities, and psychological welfare. Conclusions This Delphi study establishes expert-endorsed principles for the care of physically trapped patients following MVCs. Adoption of these principles could reduce delays, strengthen multi-agency response and improve patient outcomes. Further work is required to validate the impact of these recommendations on clinical outcomes and to support their integration into practice through policy development, training, and evaluation.